Rethinking Schizophrenia and Depression Comorbidity as One Psychiatric Disorder Entity: Evidence From Mouse Model - Zhou, Chunhua; Kong, Dezhi; Zhu, Xiaodong; Wu, Wei; Xue, Rong; Li, Gongying; Xu, Yong; Liu, Sha; Tian, Hongjun; Zhuo, Chuanjun (Frontiers in Neuroscience, 2020)
Schizophrenia is frequently accompanied by depressive symptoms, but the pathological mechanisms remain to be elucidated. In this study, we used chronic unpredicted mild stress (CUMS) plus MK801 injection to generate a mouse schizophrenia with depression model, in which in vivo 2-photon calcium imaging and electrophysiological recordings were performed in conjunction with behavioural phenotyping. Compared to mice models with classical depression or schizophrenia models, animal models with schizophrenia and depression comorbidity presented worse psychotic and depressive symptoms. These behavioural deficits are associated with impaired neuronal calcium activities in the frontal cortex and thalamic nuclei. Moreover, in sharp contrast to classical models that have a satisfactory response to antipsychotic or antidepressant drugs, this novel schizophrenia with depression model is resilient to combined drug treatment in terms of behavioural and functional recovery. Taken together, these data indicate that schizophrenia with depression likely involves a unique pathophysiology that is different from schizophrenia or depression alone. Key words: schizophrenia; depression; mouse model; behavioural phenotypes; prefrontal cortex (PFC) neuronal activity; antipsychotic treatment